Low-Dose Radiation Therapy Reduces Amyloid Load in Young 3xTg-AD Mice. - Ceyzériat, Kelly; Tournier, Benjamin B; Millet, Philippe; Dipasquale, Giovanna; Koutsouvelis, Nikolaos; Frisoni, Giovanni B; Garibotto, Valentina; Zilli, Thomas (J Alzheimers Dis, 2022)
BACKGROUND: Low-dose radiation therapy (LD-RT) has been shown to decrease amyloidosis or inflammation in systemic diseases and has recently been proposed as possible treatment of Alzheimer's disease (AD). A positive effect of LD-RT on tauopathy, the other marker of AD, has also been suggested. These effects have been shown in preclinical studies, but their mechanisms are still not well understood. OBJECTIVE: This study aimed to evaluate if anti-amyloid and anti-inflammatory effects of LD-RT can be observed at an early stage of the disease. Its impact on tauopathy and behavioral alterations was also investigated. METHODS: The whole brain of 12-month-old 3xTg-AD mice was irradiated with 10 Gy in 5 daily fractions of 2 Gy. Mice underwent behavioral tests before and 8 weeks post treatment. Amyloid load, tauopathy, and neuroinflammation were measured using histology and/or ELISA. RESULTS: Compared with wild-type animals, 3xTg-AD mice showed a moderate amyloid and tau pathology restricted to the hippocampus, a glial reactivity restricted to the proximity of amyloid plaques. LD-RT significantly reduced Aβ 42 aggregated forms (-71%) in the hippocampus and tended to reduce other forms in the hippocampus and frontal cortex but did not affect tauopathy or cognitive performance. A trend for neuroinflammation markers reduction was also observed. CONCLUSION: When applied at an early stage, LD-RT reduced amyloid load and possibly neuroinflammation markers, with no impact on tauopathy. The long-term persistence of these beneficial effects of LD-RT should be evaluated in future studies.